2009
DOI: 10.1111/j.1462-2920.2009.02017.x
|View full text |Cite
|
Sign up to set email alerts
|

The seasonal structure of microbial communities in the Western English Channel

Abstract: Running title: Marine bacterial seasonal succession 2 SummaryVery few marine microbial communities are well characterized even with the weight of research effort presently devoted to it. Only a small proportion of this effort has been aimed at investigating temporal community structure. Here we present the first report of the application of high-throughput pyrosequencing to investigate intraannual bacterial community structure. Microbial diversity was determined for 12 time points at the surface of the L4 samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
322
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 391 publications
(349 citation statements)
references
References 28 publications
25
322
2
Order By: Relevance
“…In addition to the spatial variation, the prokaryotic communities might be also sensitive to the seasonal variation, and this temporal dynamics might be also well represented by broadly resolved data. In fact, the original studies of cases #7 and #8 have reported clear seasonal community dynamics using order-level or class-level compositions (Gilbert et al, 2009;Yeh et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the spatial variation, the prokaryotic communities might be also sensitive to the seasonal variation, and this temporal dynamics might be also well represented by broadly resolved data. In fact, the original studies of cases #7 and #8 have reported clear seasonal community dynamics using order-level or class-level compositions (Gilbert et al, 2009;Yeh et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Spatially defined and reoccurring assessments of plankton diversity and abundance that are aligned with co-occurring environmental variables (temperature, nutrients and so on) have been used to identify the key controlling environmental drivers that influence planktonic organisms, and to form the basis of establishing the underpinning principles of their ecologies and ecosystem functional roles. For example, multi-year assessments of bacterioplankton diversity at the time series site Station L4 in the Western English Channel has shown that bacterioplankton have annually repeating seasonal-scale patterns in diversity that relate to changes in a variety of environmental drivers, including seawater temperature, seasonal diatom blooms and organic carbon availability (Gilbert et al, 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal shifts in microbial community composition have been demonstrated in marine environments, such as the Sargasso and Baltic Seas and the English Channel, where succession of microbial communities correlated with changes in mixed layer depth, temperature and nutrient concentrations throughout the year (Morris et al, 2005;Carlson et al, 2009;Gilbert et al, 2009;Andersson et al, 2010). Mixing, temperature and nutrient concentrations are important factors influencing communities in freshwater systems as well (Kent et al, 2007;Shade et al, 2008;Nelson, 2009;Berdjeb et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the large number of sequences per run (B1 million reads), 16S amplicon pyrosequencing provides better resolution of microbial biogeographical patterns, because the depth of diversity captured with each sample is greater when compared with classical community fingerprinting techniques (for example, DGGE, T-RFLP, ARISA), which only capture the most dominant species in an environment (Sogin et al, 2006). Recent studies have used 16S amplicon pyrosequencing to determine the microbial diversity of many different environments including deep sea, arctic, soil and estuarine communities (Sogin et al, 2006;Galand et al, 2009;Gilbert et al, 2009;Lauber et al, 2009;Andersson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%